(untitled) (American Journal of Business Management, Economics and Banking, 2026)
The study looks at how financial literacy affects Fintech use in Uzbekistan. It also identifies key socio-demographic factors. The findings show that financial literacy, education level, employment status, and savings rate boost Fintech usage, especially payment systems like “Click,” “Pay me,” and mobile banking. Moreover, financial literacy helps connect education and employment to Fintech usage. This underscores the need for educational programs and job opportunities to promote financial inclusion through Fintech in Uzbekistan. About 18% of the population’s openness to Fintech is explained by these factors. However, financial training does not seem to impact on Fintech usage among people.